Teaching English for Junior High School Students in Rural Area - Hafidza Nash'ul Amrina (IKIP PGRI Bojonegoro, 2023)
Abstract: Teaching English in rural area is challenging task. The teachers have many difficulties in teaching and learning process, especially in teaching four skills of English. The minimum facilities and the student’s motivation become the trigger of it. The purpose of this research was to identify the rural school facilities, second to identify the teaching English in rural area, third to identify the obstacles of teaching English in rural area. The Qualitative method was used in this research, Open ended questionnaire and interview were used to collect the data. The subject of this research was eight English teacher from eight different rural areas of junior high school in Bojonegoro. The result of this research showed that there were three main obstacles of teaching English in rural areas in Bojonegoro, first the minimum school facilities, second the low students’ motivation and mind set, and third the minimum support of parents. Abstrak: Mengajar Bahasa Inggris di daerah pelosok merupakan salah satu tugas yang menantang. Guru mempunyai banyak kesulitan dalam proses belajar mengajar, khususnya dalam pembelajaraan 4 kemampuan Bahasa Inggris. Minimnya fasilitas dan motivasi siswa menjadi pemicu dari kesulitan tersebut. Tujuan dari penelitian ini adalah untuk menidentifikasi fasilitas sekolah yang ada di pelosok, kedua untuk mengidentifikasi proses belajar mengajar Bahasa Inggris, ketiga untuk menidentifikasi kesulitan dalam hal pengajaran Bahasa Inggris di daerah pelosok. Metode kualitatif digunakan dalam penelitian ini. Kuesioner dan wawancara terbuka digunakan untuk memperoleh data. Subyek penelitian ini adalah delapan guru dari delapan Sekolah Menengah Pertama yang ada di delapan daerah pelosok Bojonegoro. Hasil dari penelitian ini menunjukan bahwa ada tiga kesulitan dalam pembelajaran Bahasa Inggris di pelosok Bojonegoro yaitu, pertama kurangnya fasilitas sekolah, kedua rendahnya motivasi dan pola pikir siswa, dan ketiga kurangnya dukungan dari orang tua.